Electrical Characterization of Sol-Gel Derived TiO2 Film on c-Si Substrate by Admittance Measurement - Ayşe Evrim Saatci; Orhan Özdemir (Advances in Materials Science and Engineering)
Transport and storage properties of sol-gel synthesized, namely, dip coating technique, titanium dioxide (TiO2) thin film over crystalline silicon (c-Si), has been investigated by means of current-voltage (I-V) and admittance analysis within different ambient. Considering the work function of anatase TiO2 film, determined by both FTIR and TG/DTA analysis, silver (Ag) as front metal electrode was chosen to hinder a barrier for charge carriers. Electrical analysis implied that Ag/TiO2/c-Si structure was actually constituted by Ag/TiO2/native silicon dioxide (SiO2)/c-Si [SIS] structure, in which SiO2 layer was identified by FTIR analysis. Consequently, the electrical features of the film were interpreted in terms of SIS diode that is capable of explaining C-V features.